Study on the gene signature related to immune microenvironment on viral and nonviral infections of hepatocellular carcinoma. Issue 15 (16th April 2021) - Qian, Hong; Song, Shanglin; Tian, Yunling; Qi, Lei; Gao, Haihong; Yuan, Lingyan
Abstract : Abstract: The pathogenesis of hepatocellular carcinoma (HCC) can be divided into viral infection (VIR) and nonviral (NVIR) infection. Two types of HCC performed different tumor immune microenvironment (TIME) which directly affected prognosis of HCC. This study aimed to identify an effective 2 types of HCC prognostic gene signature that related to immune TIME. The differential expression genes (DEGs) were analyzed by Limma R package from the Cancer Genome Atlas. Immune related genes getting from IMMport database were matched to DEGs for testing prognosis. Prognostic index (PI) consisted of prognostic immune related genes was calculated in different types of HCC by COX regression and the correlation with the abundance of immune infiltrates, including 6 type cells, via gene modules. Tumor immune estimation resource database was applied to analyze TIME. Finally, the correlations between PI of DEGs and TIICs were analyzed by the Spearman method. Results showed that PI consisted of 11 messenger RNAs in VIR and 12 messenger RNAs in NVIR groups. The PI related to HCC prognosis has different correlations with immune infiltrating cells in VIR and NVIR groups. The PI value of DEGs has significant correlations with neutrophils ( R  = 0.22, P -value = .029) and dendritic ( R  = 0.21, P -value = .036) infiltration levels in VIR group. However, in NVIR group, the result showed there were no significant correlations between PI and other 5 type cell infiltration levels ( P -value > .05). The 11-gene signature in VIR and 12-gene signature in NVIR group selected based on data from the Cancer Genome Atlas database had a different correlation with immune infiltrating cells of HCC patients. Abstract : Supplemental Digital Content is available in the text